Schistosomiasis mansoni: II - evolution of the levels of serum proteins and of their electrophoretic pattern as traced by quantitative immunoelectrophoresis - Atta, Ajax Mercês; Magalhães, Luiz Augusto; Rangel, Humberto de Araujo (Revista de Saúde Pública, 1981)
Swiss mice were infected with 100 cercariae of the Belo Horizonte strain of Schistosoma mansoni and were sacrificed weekly during eight weeks following of infection. The levels of serum protein totals in these animals did not differ from those presented by the control animals. However, serum albumin levels that were determined by rocket immunoelectrophoresis were lower during the 5th, 6th, and 7th weeks of infection. The pattern determined by crosed immunoelectrophoresis revealed alterations in serum components with mobility in the gamma and beta regions and, to a lesser degree, alpha-globulins, after oviposition by the parasite.